Efektifitas Hukum Pidana Dalam Pemberantasan Korupsi - Candra, Dr. Firman Adi (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
Corruption has many negative impacts on social life. These negative impacts include slowing economic growth, lowering the image of the government, reducing the effectiveness of resource mobilization and allocation, hampering poverty alleviation, and hindering sustainable development and development. Political corruption has an impact on the decline of democracy and damage to the political climate, thereby reducing the ability of democracy to improve the welfare of society. The poorer a country is, the more easily it is damaged by corruption because corruption in poor countries tends to undermine property rights, undermine the rule of law, and disrupt incentives for investment.